Young migrants in France. Multiliteracy activities for a reflexive process - Rispail, Marielle; Totozani, Marine; Villa-Perez, Valeria (Glottodidactica, 2022)
In this contribution, we intend to examine to what extent multiliteracy approaches make it possible to emphasize and develop various aspects of reflexivity in action in a migrant student who is in close contact with several languages within his family and school environment. To answer the source question, we gathered a corpus of various graphic and verbal signs among secondary school multilingual students that we analyzed according to a qualitative approach in the migratory and educational context of Saint-Étienne (France). It is about student output resulting from a school project that aimed at strengthening the students’ literacy competences, along with highlighting their native cultures and languages. As a reflexive tool, the depicted project turned out to be a bridge towards a multi-literacy approach, for which we have detailed the guidelines, beneficial for the learning of the French language, or the learning of any new language; it entails supporting the making of the subject in writing, then allowing an updating of the migratory experience.